The Impact of Brand Image, Perceived Price and Social Media on Purchase Intention: The Role of Brand Trust as a Mediator - Renhat Pantro Sukma; Al. Agus Kristiadi; Sigit Dani Nugroho (Jurnal Dinamika Manajemen, 2024)
Micro and small traditional culinary enterprises are desperately trying to set forth their brand image. This study aims to boost Purchase Intention supported by Brand Trust. Data were collected from 353 respondent using a simple random technique. The analysis method by PLS-SEM. Research findings showed that Brand Image andBrand Trust have a significant effect on Purchase Intention. Perceived Price and social media have no direct effect on Purchase Intention. However, both variables have significant indirect effects. These results highlight the importance of strong Brand Image and Brand Trust in shaping Purchase Intention, emphasizing the need for a holistic marketing that considers these factors while adjusting efforts regarding pricing and social media. The practical implications of this research suggest that focusing on building a positive brand image and consumer trust can increase the chances of success in marketing efforts. Moreover, the finding also highlighted that Brand Trust has paid its mediating role function significantly in supporting Brand Image and Perceived Price. Event though Social Media was not fully supported by Brand Trust, this research suggest to increase frequency of Social Media to gain a better result.